Adsorption of nanonionic surfactants on clay minerals - Junin, Radzuan (Penerbit UTM Press, 2011)
The adsorption of surfactants from aqueous solutions in porous media is very significant in the enhanced oil recovery (EOR) of oil reservoirs. Surfactant loss due to adsorption on the reservoir rocks weakens the efficiency of the chemical solution injected to decrease the oil–water interfacial tension (IFT). This study investigated the effect of the mineralogical composition of adsorbents on adsorption. Nonionic surfactants were injected into sand packs in which different amounts of clay minerals (kaolinite and illite) were added and compacted in a sand pack holder. The amount of surfactant adsorbed was quantified by subtracting the concentration of surfactants after adsorption from the initial concentration. It was concluded that there is a relationship between the adsorption of nonionic surfactants and the amount of clay mineral in the adsorbents because the quantity of surfactant adsorbed by adsorbents increased when the percentage of clay mineral in the adsorbents increased (from 2 to 8% in the sand packs). The clay mineral illite has a stronger adsorption power for nonionic surfactants than does kaolinite.